2015
DOI: 10.1113/jp271066
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine suppresses hypoxia‐induced inflammatory responses in the late‐gestation ovine fetal kidney cortex

Abstract: Key pointsr The fetus responds to decreases in arterial partial pressure of oxygen by redirecting the blood flow mainly to the brain and the heart, at a cost to other peripheral organs like the kidneys.r Renal hypoxia and ischaemia stimulate inflammatory and apoptotic responses. r Ketamine, an NMDA receptor antagonist, is able to reduce renal immune and inflammatory gene expressions stimulated by hypoxia.r Ketamine may have therapeutic potential for protection against ischaemic renal damage in fetuses subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 61 publications
6
27
0
Order By: Relevance
“…We find it interesting and intriguing that the increase in macrophages/microglia in the fetal cerebral cortex appears to be very similar to an increase in macrophages in the renal cortex of the fetus, recently reported elsewhere (Chang et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…We find it interesting and intriguing that the increase in macrophages/microglia in the fetal cerebral cortex appears to be very similar to an increase in macrophages in the renal cortex of the fetus, recently reported elsewhere (Chang et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, ketamine has been found to inhibit the inflammatory response in the fetal cerebral cortex, which undergoes transient hypoxia . In addition, ketamine can also reduce hypoxia‐mediated inflammation and apoptosis in fetal ovine kidneys . In line with these data, we and other investigators have also demonstrated that ketamine is effective in the prevention of LPS‐mediated microglial inflammation .…”
Section: Discussionsupporting
confidence: 82%
“…In a recent study, researchers intravenously administered ketamine into fetal sheep before inducing hypoxia. Ketamine ameliorated the upregulation of inflammatory pathways and reduction of metabolism caused by hypoxia [45]. Furthermore, thiopental pretreatment reduced renal IR injury induced by free radicals [46, 47].…”
Section: General Anesthesiamentioning
confidence: 99%